2011
DOI: 10.4103/0972-6748.98416
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sexuality among Indian urban school adolescents

Abstract: Context:Adolescence is a very exciting phase of life fraught with many challenges like sexuality. Understanding them is important in helping the adolescents grow up healthily.Aims:To ascertain the attitudes and knowledge about sexuality among school-going adolescents.Settings and Design:Students in two urban schools of an Indian city from class IX to XII were administered a self-reporting questionnaire on matters related to sexuality.Materials and Methods:Requisite ethical clearances were taken as also the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
1
23
2
Order By: Relevance
“…Frequently, sexuality presents, the first challenge to healthy growth and development during adolescence. Often unplanned and sometimes forced, adolescent sexual relations occur before young people acquire adequate knowledge about contraception, sexually transmitted disease or health services available to them [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, sexuality presents, the first challenge to healthy growth and development during adolescence. Often unplanned and sometimes forced, adolescent sexual relations occur before young people acquire adequate knowledge about contraception, sexually transmitted disease or health services available to them [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…12 A study among adolescents in Pune by Sathe and Sathe reported 22% of boys and less than 5% of girls having had sexual intercourse and 13.9% of adolescent had engaged in sexual intercourse with commercial sex workers. 13 In another study among classes nine to twelve students of two schools in Pune. 6.31% males and 1.31% females reported having had experienced sexual intercourse and friends constituted the main sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…It is understood the importance of these issues for teens; however the only encompass these aspects schools restrict the chance to focus on the most relevant questions from students. 9 In this environment the teacher becomes the right person to address these issues, to be a reliable and meaningful adult for the student. For this it is necessary to understand what conditions they have to fulfill this role.…”
Section: They Have To Be Aware Of the Risks Involving Sexuality That mentioning
confidence: 99%
“…Moreover, it is important not to assign ratings or notes to the work of not providing these mandatory status or something imposing. 9 Other methodological strategies can be developed in the teaching process, for better adhesion of the contents passed on if they are integrative, based on the collective nature of joint dialogue, respect reality, individuality and experiences of young people and can include the family in this process. It should focus on the doubts and seek remedy them when possible.…”
Section: How School Should Treat the Theme?mentioning
confidence: 99%
See 1 more Smart Citation